Linking diagnostic features to soil microbial biomass and respiration in agricultural grassland soil: a large‐scale study in Ireland. (22nd March 2018) - Richter, A.; Huallacháin, D. Ó.; Doyle, E.; Clipson, N.; Van Leeuwen, J. P.; Heuvelink, G. B.; Creamer, R. E.
Abstract : The functional potential of soil ecosystems can be predicted from the activity and abundance of the microbial community in relation to key soil properties. When describing microbial community dynamics, soil physicochemical properties have traditionally been used. The extent of correlations between properties, however, differs between studies, especially across larger spatial scales. In this research we analysed soil microbial biomass and substrate‐induced respiration of 156 samples from Irish grasslands. In addition to the standard physicochemical, soil type and land management variables, soil diagnostic properties were included to identify if these important soil–landscape genesis classes affected microbial biomass and respiration dynamics in Irish soil. Apart from physicochemical properties, soil drainage class was identified as having an important effect on microbial properties. In particular, biomass‐specific basal (qCO2 ) and substrate‐induced respiration (SIR:CFE) were explained best by the soil drainage. Poorly drained soil had smaller values of these respiration measures than well‐drained soil. We concluded that this resulted from different groups within the microbial community that could use readily available carbon sources, which suggests a change in microbial community dynamics associated with soil texture and periods of water stress. Overall, our results indicate that soil quality assessments should include both physicochemical properties and diagnostic classes, to provide a better understanding of the behaviour of soil microbial communities. Highlights: Assessing the effect of soil diagnostic features and properties on microbial biomass and respiration A soil biological survey from 156 grassland sites in Ireland Soil drainage class has an important effect on microbial properties Soil quality assessments should include both physicochemical properties and diagnostic classes